The ToMenovela – A Photograph-Based Stimulus Set for the Study of Social Cognition with High Ecological Validity - Herbort, Maike C.; Iseev, Jenny; Stolz, Christopher; Roeser, Benedict; Großkopf, Nora; Wüstenberg, Torsten; Hellweg, Rainer; Walter, Henrik; Dziobek, Isabel; Schott, Björn H. (Frontiers in Psychology, 2016)
We present the ToMenovela, a stimulus set that has been developed to provide a set of normatively rated socio-emotional stimuli showing varying amount of characters in emotionally laden interactions for experimental investigations of i) cognitive and ii) affective ToM, iii) emotional reactivity, and iv) complex emotion judgment with respect to Ekman’s basic emotions (happiness, sadness, anger, fear, surprise and disgust, Ekman & Friesen, 1975). Stimuli were generated with focus on ecological validity and consist of 190 scenes depicting daily-life situations. Two or more of eight main characters with distinct biographies and personalities are depicted on each scene picture. To obtain an initial evaluation of the stimulus set and to pave the way for future studies in clinical populations, normative data on each stimulus of the set was obtained from a sample of 61 neurologically and psychiatrically healthy participants (31 female, 30 male; mean age 26.74 +/- 5.84), including a visual analog scale rating of Ekman’s basic emotions (happiness, sadness, anger, fear, surprise and disgust) and free-text descriptions of the content. The ToMenovela is being developed to provide standardized material of social scenes that are available to researchers in the study of social cognition. It should facilitate experimental control while keeping ecological validity high.